2014
DOI: 10.3928/01477447-20140528-56
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra-articular Injection of Tranexamic Acid on Postoperative Hemoglobin in Total Hip Arthroplasty

Abstract: Postoperative anemia is a significant risk factor in total hip arthroplasty, leading to increased length of hospital stay and delayed mobility and rehabilitation, and is poorly tolerated by patients with peripheral vascular and cardiovascular disease. Intravenous tranexamic acid, an antifibrinolytic drug, has been shown to reduce postoperative anemia in total joint replacement. Intra-articular administration eliminates the risk of systemic effects, the most concerning of which is thrombosis. Although this meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…The potential advantages of topical application of TXA were direct targeting of the site of bleeding and prevention of systemic adverse effects . Several studies reported that topical use of TXA (10 mg/kg; 3 g) was also effective in reducing postoperative blood loss in THA . The second phase showed that postoperative blood loss was significantly lower in the TITA group than that of the IVTA‐II group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential advantages of topical application of TXA were direct targeting of the site of bleeding and prevention of systemic adverse effects . Several studies reported that topical use of TXA (10 mg/kg; 3 g) was also effective in reducing postoperative blood loss in THA . The second phase showed that postoperative blood loss was significantly lower in the TITA group than that of the IVTA‐II group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the growing perioperative use of tranexamic acid (TXA) demonstrated its efficacy in reducing blood loss and postoperative transfusions after THA . Several investigators sought to elicit the clinical outcomes of TXA in total joint arthroplasty, and the majority of their studies utilized intravenous (IV) administration of TXA, many of which involved the administration of multiple doses .…”
mentioning
confidence: 99%
“…However, there are still controversy about the efficacy of TXA in THA. Some studies reported better outcomes in TXA for reducing blood loss [ 14 – 23 ] while other studies found no differences for transfusion rates [ 24 27 ] between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Proponen que utilizando el fármaco de forma local podría aumentarse su concentración en la región de interés, mejorando por tanto su efectividad y disminuyendo además los efectos secundarios (que estarían producidos mayoritariamente por el reparto sistémico del TXA). Muchos autores posteriormente han corroborado la eficacia y seguridad de esta vía, tanto en las prótesis de cadera como en las prótesis de rodilla (88,180,186,(194)(195)(196)(197)(198)(199).…”
unclassified
“…La variable principal a estudio fue la tasa de transfusión o porcentaje de pacientes transfundidos dentro del grupo TXA y dentro del grupo control. proporción la más habitual en la literatura (88,166,167,169,184,197,203).…”
unclassified